Hubungan Preeklampsia dengan Kejadian Asfiksia Neonatorum Pada Bayi Baru Lahir - Ketut Esti Rosdiana; Ni Ketut Somoyani; Ni Komang Erny Astiti (Journal Center of Research Publication in Midwifery and Nursing, 2026)
Background: Preeclampsia is a common pregnancy complication that can lead to severe neonatal outcomes. This study aimed to investigate the relationship between maternal preeclampsia and the incidence of neonatal asphyxia. Method: Using an analytical correlational design with a case–control approach, this study was conducted at Wangaya Regional General Hospital, Denpasar, from April 29 to May 29, 2025. It evaluated 166 newborns, divided equally into a case group (83 with asphyxia) and a control group (83 without asphyxia). Secondary medical record data were collected, and bivariate analysis was performed using the Chi-square test (alpha = 0.05). Results: Within the study sample, the prevalence of preeclampsia was 43.4%. The analysis revealed a statistically significant association between maternal preeclampsia and neonatal asphyxia (p = 0.008), with an Odds Ratio (OR) of 2.456. This indicates that infants born to preeclamptic mothers face a substantially higher risk of developing asphyxia. Conclusions: There is a significant association between maternal preeclampsia and neonatal asphyxia. These findings underscore the critical importance of optimizing clinical management for pregnant women with preeclampsia to mitigate the risk of neonatal asphyxia and improve newborn outcomes